PENGARUH KUALITAS PRODUK DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PENGGUNAAN JASA EDITH WEDDING ORGANIZER BEKASI - Indah Purnamasari; Adelina Suryati; Darmeinis (STKIP Subang, 2026)
This study aims to analyze the influence of Product Quality (X1) and Price Perception (X2) on the Decision to Use Services (Y) at Edith Wedding Organizer Bekasi. The Wedding Organizer industry currently faces challenges due to declining marriage rates and fierce competition in Jabodetabek. This quantitative study utilized a sample of 60 respondents who are clients of Edith Wedding Organizer, selected via convenience sampling. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) via SmartPLS 4.0. The results show that Product Quality has a positive and significant partial effect on Service Use Decision (original sample = 0.362; t-statistic = 2.101; p-value = 0.018). Price Perception also has a positive and significant partial effect (original sample = 0.567; t-statistic = 3.359; p-value = 0.000). Simultaneously, both variables significantly affect the decision with R² = 0.821 (82.1%), while the remaining 17.9% is influenced by other factors. Price Perception was found to be more dominant than Product Quality, indicating high customer price sensitivity.